Cáncer de mama HER2 bajo en un hospital nacional de Lima, Perú: análisis retrospectivo 2020–2024 - Asencio Aguedo, Angélica Yeyli (2026)
Introduction: Breast cancer is the most common malignant neoplasm amongwomen worldwide. Treatment has traditionally been guided by the expression of hormone receptors and other proteins related to cell proliferation, such as HER2 and Ki-67. HER2 status has been a key factor in therapeutic decision-making due tothe availability of targeted therapies. However, recent studies have proposed the existence of a possible subgroup within HER2-negative tumors referred to as HER2-low that may benefit from new treatment options. Objective: To identify the proportion of breast cancer cases that could be classified as HER2-low in a national hospital in Peru. Methods: Observational, analytical, cross-sectional, and retrospective study. A total of 1,575 patients with a histopathological diagnosis of breast cancer were included, covering the period from 2020 to 2024. Results: Among all analyzed cases, the HER2-low subtype represented 37.6% of total breast cancer cases and 50.6% of those previously categorized as HER2-negative. Hormone receptor (HR) expression was more frequently observed in HER2-low tumors compared to HER2 0 and HER2- positive subtypes. Conclusions: HER2-low breast cancer accounts for a significant proportion of total cases, highlighting the importance of accurate molecular profiling.This subgroup could potentially benefit from newly emerging targeted therapies.